Exploring EFL Students’ Experience in Developing Daily Lesson Plan for Teaching English for Toddler - Noor Aida Aflahah; Hafizhatu Nadia (ELLITE, 2022)
Planning English for Toddler lesson is a sophisticated process faced by English as Foreign Language (EFL) students. The lesson plan should be available before implementation to increase the effective teaching process. By having a different lesson plan template to a regular lesson plan, this study explores EFL student experience in developing daily lesson plans for teaching English to toddlers. A narrative approach was employed in this study. The subjects of this study were 6th semester EFL students who took English for Toddler course. Drawing on semi-structured interview data, we found that students face several challenges in developing daily lesson plans for teaching English to toddlers. Participants experienced challenges in preparing content in a lesson plan, learning media, model, teaching method, and assessment. This study emphasizes the importance of training of developing a lesson plan for teaching English for toddler. Further studies will facilitate EFL students' skills to develop a lesson plan for teaching English for Toddler.